A dynamic reciprocal RBR-PRC2 regulatory circuit controls Arabidopsis gametophyte development - Johnston, Amal Joseph; Matveeva, Elena; Kirioukhova, Olga; Grossniklaus, Ueli; Gruissem, Wilhelm (Current biology, 2008)
Summary. Unlike animals that produce gametes upon differentiation of meiotic products, plants develop haploid male and female gametophytes that differentiate gametes such as sperm, egg and central cells, and accessory cells [1, 2]. Both gametophytes participate in double fertilization and give rise to the next sporophytic generation. Little is known about the function of cell-cycle genes in differentiation and development of gametophytes and in reproduction [1, 2]. RETINOBLASTOMA RELATED (RBR) is a plant homolog of the tumor suppressor Retinoblastoma (pRb), which is primarily known as negative regulator of the cell cycle [3]. We show that RBR is required for cell differentiation of male and female gametophytes in Arabidopsis and that loss of RBR perturbs expression levels of the evolutionarily ancient Polycomb Repressive Complex 2 (PRC2) subunits and their modifiers encoding PRC2 subunits or DNA METHYLTRANSFERASE 1 (MET1) [4-6], exemplifying convergent evolution involving the RBR-PRC2-MET1 regulatory pathways. In addition, RBR binds MET1, and maintenance of heterochromatin in central cells, a mechanism that is likely mediated by MET1 [7, 8], is impaired in the absence of RBR. Surprisingly, PRC2-specific H3K27-trimethylation activity represses paternal RBR allele, suggesting a functional role for a dynamic and reciprocal RBR-PRC2 regulatory circuit in cellular differentiation and reproductive development.